Local Venturing as Compassion Organizing in the Aftermath of a Natural Disaster: The Role of Localness and Community in Reducing Suffering - Shepherd, Dean A.; Williams, Trenton A. (Journal of Management Studies, 2014)
AbstractIn contrast to models of compassion within existing organizations, this grounded theory study examines how ventures emerge relying on localness and community in direct response to ‘opportunities’ to alleviate suffering in the aftermath of a natural disaster. While a natural disaster is a surprising disruptive event devastating a local community, that local community is nested within a broader community, which can be a source of abundant resources. Ventures created in the aftermath of a natural disaster, given local knowledge and unencumbered by pre‐existing systems, procedures, and capabilities, are highly effective at connecting the broader community with the local community through customizing resources to meet victims' needs and to quickly delivering these resources to alleviate suffering.